Review of Carbon Dioxide Capture and Storage With Relevance to the South African - (:unkn) unknown (My University, 2013)
The issue of carbon dioxide emissions and its link to climate change is currently a major discussion point in government and amongst the public at large in South Africa, especially due to the country's heavy reliance on fossil fuels for electricity production. This paper provides a review on the current situation regarding carbon dioxide (CO 2) emissions in the South African power generation sector, and potential process engineering solutions to reduce these emissions. Estimates of CO 2 emissions are presented, with the main sources of emissions identified and bench-marked to other countries. A promising mid-term solution for mitigation of high CO 2 emissions, known as carbon dioxide capture and storage (CCS), is reviewed. The various aspects of CCS technology and techniques for CO 2 capture from pulverised coal power plants are discussed, which include processes such as gas absorption, hydrate formation, cryogenic separation, membrane usage, sorbent usage, enzyme-based systems, and metal organic frameworks. The latest power plant designs which optimise CO 2 capture are also discussed and include integrated gasification combined cycle (IGCC), oxy-fuel combustion, integrated gasification steam cycle (IGSC), and chemical looping combustion. Each CO 2 capture technique and plant modification is presented in terms of the conceptual idea, the advantages and disadvantages, and the extent of development and applicability in a South African context. Lastly, CO 2 transportation, storage, and potential uses are also presented. The main conclusions of the review are that gas absorption using solvents is currently most applicable for CO 2 capture and that enhanced coal bed methane recovery could provide the best disposal route for CO 2 emissions mitigation in South Africa.
Keywords: African Research